Thyroid leiomyosarcoma: presentation of two cases and review of the literature - Şahin,Mehmet İlhan (2016)
Abstract Introduction: Leiomyosarcoma is a tumor which is rarely seen in the thyroid gland. The diagnosis may be difficult and the treatment is controversial. Objective: The objective of the study is to review the literature about a rare malignant disease of the thyroid gland which has high mortality. Methods: Two cases of thyroid leiomyosarcoma are presented and the previous 23 cases in the current literature are reviewed. Results: A total of 25 cases of thyroid leiomyosarcoma are reviewed; the most common complaint was rapidly growing anterior neck mass, and ten of the 25 patients had distant metastasis at the initial admission. Fifteen of the 25 patients died with the disease in the first 12 months after the diagnosis. Conclusion: The differential diagnosis of thyroid leiomyosarcoma is important and should be performed with other malignancies of the gland, especially with anaplastic carcinoma. The prognosis is poor and there is no consensus regarding the treatment.